The Meaning of Life of Nuns Who Serve Lepers at Bunda Pembantu Abadi Hospital - Mage, Mernon Yerlinda; Manafe, Rizky Pradita; Wutun, Gluseppina Kese (Universitas Nusa Cendana, 2024)
This research aims to find out how meaningful the lives of nuns who serve lepers at the Bunda Pembantu Abadi Naob Hospital, East Noemuti District, Timor Tengah Regency. This study used 5 subjects with the criteria of nuns serving lepers. This research uses descriptive qualitative methods, with two data collection methods, namely observation and interviews. The data that was obtained was analyzed using thematic analysis techniques and produced three main themes, namely, 1) self-view 2) service dynamics 3) challenges and solutions. The choice of life to become a nun with the task of serving lepers is a form of responsibility to God, oneself and others. The choice of life to become a nun leads participants to discover their self-concept and self-esteem through serving vulnerable people, namely lepers. In service, participants encounter challenges, but participants are also able to find solutions to each challenge, namely spiritual activities and an attitude of self-acceptance.